Mechanistic Clues Provided by Concurrent Changes in the Expression of Genes Encoding the M1 Muscarinic Receptor, β-Catenin Signaling Proteins, and Downstream Targets in Adenocarcinomas of the Colon - Alizadeh, Madeline; Schledwitz, Alyssa; Cheng, Kunrong; Raufman, Jean-Pierre (Frontiers in Physiology, 2022)
Muscarinic receptors (MRs) in the G protein-coupled receptor superfamily are recipients and mediators of parasympathetic neural transmission within the central and enteric nervous systems. MR subtypes, M1R-M5R, encoded by CHRM1-CHRM5, expressed widely throughout the gastrointestinal (GI) tract, modulate a range of critical, highly regulated activities in healthy tissue, including secretion, motility, and cellular renewal. CHRM3/M3R overexpression in colon cancer is associated with increased cell proliferation, metastasis, and a worse outcome, but little is known about the role of the other four muscarinic receptor subtypes. To address this gap in knowledge, we queried the NCI Genomic Data Commons for publicly available TCGA-COAD samples collected from colon tissue. RNA-seq data were collected and processed for all available primary adenocarcinomas paired with adjacent normal colon. In this unbiased analysis, 78 paired samples were assessed using correlation coefficients and univariate linear regressions; gene ontologies were performed on a subset of correlated genes. We detected a consistent pattern of CHRM1 downregulation across colorectal adenocarcinomas. CHRM1 expression levels were positively associated with those for APC and SMAD4, and negatively associated with CTNNB1, the gene for β-catenin, and with coordinate changes in the expression of β-catenin target genes. These findings implicating CHRM1/M1R as an important deterrent of colon cancer development and progression warrant further exploration.